Kolams : a primitive tribe in transition - Rao, K. Mohan (Hyderabad, 1990)
Anthropological literature on the current status of Kolam Tribe which is recognised as a Primitive Tribal Group in Andhra Pradesh by Government of India for the purpose of promoting their accelerated development is scanty. Eventhough Kolams are not numerically as significant as the Gonds of Adilabad but because of their rich cultural and linguistic heritage, they constitute an important group in the planitational acculturation process decernible in this culture centre where their culture complex is found in its most representative form. Kolams have moulded the borrowed culture traits ingeneously in their cultural crucible. They are greatly influenced by Gonds in their way of life and their social organizations are identical. The traditional life styles of Kolams and changing scenario is brought out with lucid illustrations in this book which makes an interesting reading.
Keywords: Tribes